Prohibitin 1 Acts As a Negative Regulator of Wingless/Integrated‐Beta‐Catenin Signaling in Murine Liver and Human Liver Cancer Cells. Issue 12 (27th September 2018) - Mavila, Nirmala; Tang, Yuanyuan; Berlind, Joshua; Ramani, Komal; Wang, Jiaohong; Mato, José M.; Lu, Shelly C.
Abstract : Prohibitin1 ( PHB1 ) is a mitochondrial chaperone with diverse functions that include cell proliferation, apoptosis, and mitochondrial homoeostasis. Liver‐specific Phb1 knockout (KO) mice develop spontaneous injury and hepatocellular carcinoma (HCC). Our previous work demonstrated that PHB1 negatively regulates the H19‐insulin‐like growth factor 2 (IGF2)‐H19‐IGF2 axis signaling pathway and E‐box activity in hepatocytes and HCC cells. Phb1 KO livers exhibited increased expression of multiple wingless/integrated (WNT) target genes compared to control littermates. Therefore, we hypothesized that PHB1 is a negative regulator of WNT‐beta‐catenin signaling in the liver. Analysis of livers from Phb1 KO mice demonstrated an activation of the WNT‐beta‐catenin pathway as determined by phosphorylation of glycogen synthase kinase 3 (GSK3)beta serine [Ser]9 and protein kinase B (AKT) Ser473 . Phb1 KO livers showed increased messenger RNA (mRNA) levels of multiple WNT ligands, with Wnt7a (79‐fold), Wnt10a (12‐fold), and Wnt16 (48‐fold) being most highly overexpressed compared to control littermates. Subcellular fractionation of liver cells from Phb1 KO mice indicated that hepatocytes are the main source of WNT ligands. Immunostaining and cellular colocalization analysis of Phb1 KO livers demonstrated expression of WNT7a, WNT10a, and WNT16 in hepatocytes. Chromatin immunoprecipitation revealed increased binding of transcription factor E2F1 (E2F1) to the Wnt10a promoter in Phb1 KO livers and WNT9A in HepG2 cells. PHB1 silencing in HepG2 cells activated WNT signaling, whereas its overexpression caused inactivation of this pathway. PHB1 silencing in HepG2 cells induced the expression of multiple WNT ligands of which WNT9A induction was partly regulated through E2F1. Conclusion: PHB1 acts as a negative regulator of WNT signaling, and its down‐regulation causes the induction of multiple WNT ligands and downstream activation of canonical WNT‐beta‐catenin signaling in murine liver and human HCC cells, in part through E2F1.